2006
DOI: 10.1038/sj.cdd.4401914
|View full text |Cite
|
Sign up to set email alerts
|

p53/p63/p73 isoforms: an orchestra of isoforms to harmonise cell differentiation and response to stress

Abstract: Abstractp63, p73 and p53 compose a family of transcription factors involved in cell response to stress and development. p53 is the most frequently mutated gene in cancer (50%) and loss of p53 activity is considered to be ubiquitous to all cancers. Recent publications may have a profound impact on our understanding of p53 tumour suppressor activity. p63, p73 and p53 genes have a dual gene structure conserved in drosophila, zebrafish and man. They encode for multiple p63, p73 or p53 proteins containing different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
518
1
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 469 publications
(543 citation statements)
references
References 72 publications
(78 reference statements)
11
518
1
4
Order By: Relevance
“…2, be divided into three regions: the N-terminal region with at least two alternative forms, the central part which is conserved in all the sequences and the C-terminal region again with at least two alternative forms. As already discussed by other authors (Goodson et al, 2006), this suggests we here deal with alternative sequences originating from the same gene, which is not surprising given that all p53 family genes are able to express alternative products (Murray-Zmijewski et al, 2006).…”
Section: Other Molluscan P53 Family Sequencessupporting
confidence: 60%
See 3 more Smart Citations
“…2, be divided into three regions: the N-terminal region with at least two alternative forms, the central part which is conserved in all the sequences and the C-terminal region again with at least two alternative forms. As already discussed by other authors (Goodson et al, 2006), this suggests we here deal with alternative sequences originating from the same gene, which is not surprising given that all p53 family genes are able to express alternative products (Murray-Zmijewski et al, 2006).…”
Section: Other Molluscan P53 Family Sequencessupporting
confidence: 60%
“…The central region of all p53 family sequences codes for the DNA binding domains and is very similar in all members of the family (Murray-Zmijewski et al, 2006). Within the phylum of mollusks, all the sequences originating from the same species have an identical or almost identical central region (differing in up to a few single nucleotide differences in almost 1kb of DNA sequence).…”
Section: Other Molluscan P53 Family Sequencesmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, the full-length TA versions of p63/p73 can exert p53-like activities, whereas the DN versions have the opposite effect (reviewed by Yang et al, 2002). More recently it was reported that p53 can also be expressed as multiple isoforms differing in N and C-termini (reviewed by Murray-Zmijewski et al, 2006). The different p53 C-termini, however, are quite distinct from those of p63 and p73.…”
Section: Introductionmentioning
confidence: 99%